Effects of supplemental degradable intake protein on intake and digestibility of low-quality brome hay - C.P. Mathis; R.C. Cochran; J.S. Heldt; B.C. Woods; Gerald L. Stokka; K. C. Olson; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 1998)
The effects of increasing levels of degradable intake and digestion of low-quality brome hay were evaluated using 16 ruminally fistulated beef steers. Trends were evident for small, positive changes in total intake and digestion with increasing level of DIP supplementation. As a result, total digestible to feeding forage to provide .041, .082, and OM intake (TDOMI) increased with DIP supplementation but tended to plateau below the highest supplementation level.
Keywords: Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 804; Cattlemen& #x27; s Day; 1998; Beef; Steers; Forage; Intake; Digestion; Degradable intake protein